Navigating Borders: The Impact of Migrant Networks on Citizenship and Security in Sabah, Malaysia - Othman, Zaini (Journal of Ecohumanism, 2024)
This article explores the dynamics of migrant networks, citizenship, and security in Sabah, focusing on the experiences of Filipino and Indonesian migrant communities. Through a qualitative and ethnographic methodology, conducted over 12 months from January to December 2023, the study investigates how these networks support migrants in navigating complex legal frameworks and social challenges, while also shaping local perceptions and governmental policies. The findings reveal that despite their significant contributions to Sabah’s economy and cultural diversity, migrants face substantial barriers to legal recognition and social acceptance. The interplay between migrant networks and citizenship rights highlights the need for more nuanced migration policies that promote integration rather than marginalization. As security concerns increasingly influence governmental responses, this article argues for a balanced approach that safeguards national interests while upholding human rights. The research underscores the importance of inclusive policies that facilitate pathways to legal residency, ensure access to basic services, and foster community engagement. Ultimately, the experiences of migrant communities in Sabah offer valuable lessons for other regions facing similar challenges in the context of globalization.